Semisolid-lubricant-based ball-bearing triboelectric nanogenerator for current amplification, enhanced mechanical lifespan, and thermal stabilization. (March 2022) - Song, Myunghwan; Chung, Jihoon; Chung, Seh-Hoon; Cha, Kyunghwan; Heo, Deokjae; Kim, Sunghan; Hwang, Patrick T.J.; Kim, Dongseob; Koo, Bonwook; Hong, Jinkee; Lee, Sangmin
Abstract: Triboelectric nanogenerators (TENGs) represent a promising tool for harvesting mechanical energy and can generate electrical output through the surface charge of materials. However, because this conversion is based on contact electrification, frictional contact inevitably occurs between materials, and the high surface charge considerably limits the electrical output of TENGs. To effectively decrease the frictional wear of triboelectric materials, commercial lubricants can be applied while ensuring a suitable mechanical structure design. In this study, we demonstrated a ball-bearing-type TENG with a commercial semisolid lubricant, which could overcome the mechanical and electrical limitations of conventional TENGs. The application of a nonpolar semisolid lubricant on the surface of triboelectric materials could effectively suppress air breakdown and enhance the mechanical lifespan of the device by reducing friction. Owing to the reduced wear and enhanced thermal stability, the ball-bearing-type TENG could generate a consistent electrical output for over 55 h of continuous operation. Graphical Abstract: ga1 Highlights: Bearing type TENG using commercial semisolid lubricant for enhancing mechanical and electrical performance. Enhancing thermal stability and mechanical lifespan through applying lubricant on the TENG surface. High current generation through suppressing air breakdown and metal-metal contact.